Standardized ETDRS charts for mobile devices - Kędzierska, Ewelina Agnieszka; Petelczyc, Krzysztof; Kakarenko, Karol; Bieda, Marcin; Kowalczyk, Adam; Byszewska, Anna; Kolodziejczyk, Andrzej (Photonics Letters of Poland, 2017)
Charts displayed on mobile devices was verified in comparison to standardized ETDRS charts. Such method of visual acuity assessment is characterized by stabile brightness and contrast. Moreover the ability to dynamically display random optotypes eliminates the problem of memorizing the contents of charts, making measurements more reliable. Our tests showed that the VA measured with mobile device and the VA tested using standardized printed charts are not significantly different. Full Text: PDF References B. Shneiderman, Leonardo’s Laptop: Human Needs and the New Computing Technologies (Boston, MIT Press 2002). A. Holzinger, M. Errath, "Mobile computer Web-application design in medicine: some research based guidelines", P. Univ. Access Inf. Soc. 6, 31 (2007). CrossRef R. K. Lord et al., "Novel Uses of Smartphones in Ophthalmology", Ophthalmology 117, 1274 (2010). CrossRef M. D. Crossland, R. S. Silva and A. F. Macedo, "Smartphone, tablet computer and e-reader use by people with vision impairment", Ophthalmic Physiol. Opt. 34, 552 (2014). CrossRef E. Zvornicanin, J. Zvornicanin and B. Hadziefendic, "The Use of Smart phones in Ophthalmology", Acta Inform. Med. 22, 206 (2014). CrossRef S. Tofigh et al., "Effectiveness of a smartphone application for testing near visual acuity", Eye 29, 1464 (2015). CrossRef C. Perera et al., "The Eye Phone Study: reliability and accuracy of assessing Snellen visual acuity using smartphone technology", Eye 29, 888 (2015). CrossRef Department of Epidemiology and Preventive Medicine, Early Treatment Diabetic Retinopathy Study: Manual of Operations. (Baltimore, U.S. Department of Commerce 1985). F. L. Ferris et al., "New Visual Acuity Charts for Clinical Research", Am. J. Ophthalmol. 94, 91 (1982). CrossRef W. F. Long, G. C. S. Woo, "Measuring Light Levels with Photographic Meters", Optometry Vision Sci. 57, 51 (1980). CrossRef F. L Ferris, R. D. Sperduto, "Standardized Illumination for Visual Acuity Testing in Clinical Research", Am. J. Ophthalmol. 94, 97 (1982). CrossRef Ch. Dancey, J. Reidy, Statistics Without Maths for Psychology (Harlow, Prentice Hall 2011). N. Balakrishnan, Methods and applications of statistics in the life and health sciences (New Jersey, John Wiley & Sons 2010). ISO 8596:2009 Ophthalmic optics - Visual acuity testing - Standard optotype and its presentation (2009). S. Koenig et al., "Assessing visual acuity across five disease types: ETDRS charts are faster with clinical outcome comparable to Landolt Cs", Graefes Arch. Clin. Exp. Ophthalmol. 252, 1093 (2014). CrossRef A. Glasser, M. W. C. Campbell, "Presbyopia and the optical changes in the human crystalline lens with age", Vision Research 38, 209 (1998). CrossRef P. K. Kaiser, "Prospective Evaluation of Visual Acuity Assessment: A Comparison of Snellen Versus ETDRS Charts in Clinical Practice (An AOS Thesis)", Trans. Am. Ophthalmol. Soc. 107, 311 (2009). DirectLink L. Hyvärinen, R. Näsänen and P. Laurinen, "New Visual Acuity Test For Pre-School Children", Acta Ophthalmol. 58, 507 (1980). CrossRef M. Schuster, "Speech Recognition for Mobile Devices at Google", Lecture Notes in Computer Science 6230 (2010). CrossRef M. Werner, M. Kessel and C. Marouane, "Indoor positioning using smartphone camera", IPIN, International Conference on. IEEE (2011). CrossRef